Contrapontos entre o masculino e o feminino em São Bernardo, de Graciliano Ramos - Silva, Janaina Angela da (2009)
Our study analyses the novel São Bernardo, by Graciliano Ramos, published in 1934. Our perspective is interested in the tensions established between the two main characters - Paulo Honório e Madalena, both representing specific poles attached to the masculine and the feminine. Along our study we try to contextualized the historical period represented by the author, as well as the gender and social arrangements of those days. Language and discourse are presented as possible tools of balancing the gendered tensions established in the organization of power. Gender studies as well as language perspectives on discourse are our main elements to analyze the novel chosen for our corpus. We believe tension does not finish at the end of the novel, but it is displaced to another level. Writing appears as the only element that might help in bringing the whole system (of the novel) into balance